Separation of Olein-Stearin from Crude Palm Oil at Different Temperatures and Solvents by Centrifugation - Sangwichien, Chayanoot; Chandumpai, Ausa (Asian Journal of Chemistry, 2010)
This work accounts with separation of olein-stearin from crude palm oil by centrifugation at different temperatures (ambient temperature, 0, -25 and -80 ºC) and solvents (acetone, 2-propanol, 1-butanol and diethyl ether). Melting characteristics, triglycerides contents and fatty acid compo-sitions in crude palm oil and stearin fractions at the different conditions were analyzed. Since crude palm oil samples at temperature below 0 ºC were in solid state, separation by centrifugation could not be carried out. It was also difficult to maintain the solutions at the given temperatures throughout an experiment; therefore, effects of solvent polarity were performed only at ambient temperature. Among the experimental conditions, the highest percent yield of stearin (12.03 %) was obtained from crude palm oil dissolved in 2-propanol, while 10.18 % was from crude palm oil sample. Triglyceride is a major constituent (92.5-100 %) in all the separated stearins. Studying on melting characteristics indicated that the stearin obtained from crude palm oil at ambient temperature has the lowest melting point, while the others do not correspond with solvent polarity index. In addition, analysis of fatty acid using GLC with capillary column showed that crude palm oil sample might comprise of some fatty acids which are not commonly found in biological materials and is under determined in this laboratory.